The needs and preferences of pregnant smokers regarding tailored Internet-based smoking cessation interventions: a qualitative interview study - Herbec, Aleksandra (BioMed Central, 2014)
BACKGROUND: Internet-based Smoking Cessation Interventions (ISCIs) may help pregnant smokers who are unable, or unwilling, to access face-to-face stop smoking support. Targeting ISCIs to specific groups of smokers could increase their uptake and effectiveness. The current study explored the needs and preferences of pregnant women seeking online stop smoking support with an aim to identify features and components of ISCIs that might be most attractive to this population. METHODS: We conducted qualitative interviews with thirteen pregnant women who completed the intervention arm of a pilot randomized controlled trial of a novel ISCI for pregnant smokers (‘MumsQuit’). The interviews explored women’s views towards MumsQuit and online support with quitting smoking in general, as well as their suggestions for how ISCIs could be best targeted to pregnancy. Interview transcripts were analyzed using Framework Analysis. RESULTS: Participants expressed preferences for an accessible, highly engaging and targeted to pregnancy smoking cessation website, tailored to individuals’ circumstances as well as use of cessation medication, offering comprehensive and novel information on smoking and quitting smoking in pregnancy, ongoing support with cravings management, as well as additional support following relapse to smoking. Participants also viewed as important targeting of the feedback and progress reports to baby’s health and development, offering personal support from experts, and providing a discussion forum allowing for communication with other pregnant women wanting to quit . CONCLUSIONS: The present study has identified a number of potential building blocks for ISCIs targeted to quitting smoking in pregnancy. Pregnant smokers willing to try using ISCI may particularly value an engaging intervention offering a high degree of targeting of comprehensive information to them as a group and tailoring support and advice to their individual needs, as well as one providing post-relapse support, peer-to-peer communication and personal support from experts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2458-14-1070) contains supplementary material, which is available to authorized users.